Effect of Age and Sex on the Growth and Carcass Characteristics of Giriraja Birds and Selection of Ideal Slaughter Age - Kogilasan, D; Mandal, P K; Venugopal, S; Pal, U K; Kasthuri, S; Gawdaman, G (Journal of Meat Science, 2026)
An experiment was conducted with the aim to examine the effect of age and sex  on growth and slaughter characteristics of Giriraja birds to find the ideal age  of slaughter. A total of 100 day old Giriraja chicks were procured and divided  into two groups viz., male (47 birds) and female (53 birds) after completion  of 6 weeks of age. Growth and feed consumption was recorded till 12th week.  Six birds each from male and female were slaughtered every week from 8 to  12 weeks as per the standard procedures and all the slaughter and carcass  data were collected. In male and female Giriraja birds, the highest weekly  body weight gain was recorded in 11th and 5th weeks, respectively, which were  significantly (P
Keywords: Giriraja birds; pre-slaughter weight; feed conversion ratio; age of slaughter; carcass characteristics.